(untitled) - Miller, Kayla; Lome, Jess; Prescott, Lor; Knight, Thorn (New York, NY, 2025)
"Olive is excited to reunite with Max and Bree at Camp Acorn Lake, but the buses have barely pulled away when her two closest camp friends start fighting--and it's not just a little squabble. They refuse to speak to each other and, even worse, try to make Olive choose sides. ... With Willow enjoying her busy activity and social schedule, Olive has no choice but to spend most of her time with unhappy first-time camper Nat. It's far from the fun-filled, sun-filled summer she had planned. Luckily, Olive is able to distract herself with a new challenge: pitching a winning plan for improving the camp. Willow, Nat, and even the feuding Max and Bree want to help Olive make the camp a better place, but with all the drama, they're lacking the teamwork to make the dream work. Can Olive find a way to free herself and her friends from everything that's holding them back or are they doomed to stay stuck in their disagreements?"--
Keywords: Fighting (Psychology); Cartoons and comics; Graphic novels; Fiction; Camps; Fiction; Vendetta; Fiction; Fiction; Fiction; Best friends; Comic books, stips, etc; Friendship in children; Friendship; Best friends; Comic books, strips, etc; Fighting (Psychology); Comic books, strips, etc; Vendetta; Comic books, strips, etc; Camps; Comic books, strips, etc; Graphic novels